Disentangling Drought and Nutrient Effects on Soil Carbon Dioxide and Methane Fluxes in a Tropical Forest - Bréchet, Laëtitia; Courtois, Elodie A.; Saint-Germain, Thomas; Janssens, Ivan A.; Asensio, Dolores; Ramirez-Rojas, Irene; Soong, Jennifer L.; Van Langenhove, Leandro; Verbruggen, Erik; Stahl, Clément (Frontiers in Environmental Science, 2019)
Tropical soils are a major contributor to the balance of greenhouse gas (GHG) fluxes in the atmosphere. Models of tropical GHG fluxes predict that both the frequency of drought events and changes in atmospheric deposition of nitrogen (N) will significantly affect dynamics of soil carbon dioxide (CO2) and methane (CH4) production and consumption. In this study, we examined the combined effect of a reduction in precipitation and an increase in nutrient availability on soil CO2 and CH4 fluxes in a primary French Guiana tropical forest. Drought conditions were simulated by intercepting precipitation falling through the forest canopy with tarpaulin roofs. Nutrient availability was manipulated through application of granular N and / or phosphorus (P) fertilizer to the soil. Soil water content (SWC) below the roofs decreased rapidly and stayed at continuously low values until roof removal, which as a consequence roughly doubled the duration of the dry season. After roof removal, SWC slowly increased but remained lower than in the control soils even after 2.5 months of wet-season precipitation. We showed that drought-imposed reduction in SWC decreased the CO2 emissions (i.e CO2 efflux), but strongly increased the CH4 emissions. N, P and N × P (i.e. NP) additions all significantly increased CO2 emission but had no effect on CH4 fluxes. In treatments where both fertilization and drought were applied, the positive effect of N, P and NP fertilization on CO2 efflux was reduced. After roof removal, soil CO2 efflux was more resilient in the control plots than in the fertilized plots while there was only a modest effect of roof removal on soil CH4 fluxes. Our results suggest that a combined increase in drought and nutrient availability in soil can locally increase the emissions of both CO2 and CH4 from tropical soils, for a long term.